Preparing for the Challange of Governance in International Economic Relations in the 21st Century: A Plea to the Indonesian Legal Profession - Kartadjoemena, H. S. (Indonesian Journal of International Law, 2004)
It is a common knowledge that globalization has connected the relations between states, organizations, economists, and also the interaction between them. This following article, as already stated on the title, is very influencing and challenging, and also at the same time pushing the jurists in Indonesia to involve in international forums on this 21th century. Although the role of jurists in Indonesia isless significant concerning the consequences of the weakness of legal system order in Indonesia, but they have to be prepare facing the issues as the concequences of globalization and the growing of international organizations, such as: WTO, ASEAN Free Trade, et cetera. The skill of Indonesian jurists can not be limited only into good skill, knowledge, ethics, and national issues, but also has to be expand into international scope, to strengthen theirselves with foreign jurists and also to bring national interest in every international forum discussion.